Accounting Standard for Private Entities: are They Truly Useful? (Survey among Accounting Stakeholders in West Java, Indonesia) - Pratama, Arie; Ismail, Rina Fadhilah; Muhammad, Kamaruzzaman; Yadiati, Winwin (Journal of Ecohumanism, 2024)
This study examines the usefulness of new accounting standards for Indonesian private entities namely the Indonesian Private Entity Financial Accounting Standard (SAK EP), which will come into effect in 2025, in preparing private entities’ financial statements, from the perspective of various stakeholders: accounting students, accounting educators, financial statement preparers, and financial statement users. It is a simplified accounting framework that is tailored to smaller entities without public accountability and less complexity in reporting financial information while retaining essential information in meeting stakeholders’ need. This study uses two independent variables from accounting decision usefulness theory: (1) accounting stakeholders’ level of understanding of the SAK EP and (2) accounting stakeholders’ perceptions of the accounting profession. This study collected data from 515 accounting stakeholders in West Java Province, Indonesia, through an online survey. A quantitative research method is employed, and the data is analysed using two key statistical techniques: (1) one-way ANOVA to assess whether there are statistically significant differences in the mean scores of accounting stakeholders, and (2) multiple regression analysis to examine the relationship between the dependent variable (usefulness) and two independent variables (level of understanding of the SAK EP and perception of the accounting profession). The findings showed that: (1) the level of understanding of SAK EP varies among accounting stakeholders; (2) the perception of accounting stakeholders toward the accounting profession is generally high ; (3) the usefulness of SAK EP in preparing high-quality financial statements is highly perceived and (4) high understanding of the SAK EP and better perception of the accounting profession increase the usefulness of the SAK EP standard in the preparation of financial statements among private entities. This study suggests that the implementation of SAK EP in Indonesia is quite challenging, especially in improving the understanding of SAK EP and meeting high expectations of accounting stakeholders.